Obszary badawcze glottodydaktyki - Wilczyńska, Weronika (Neofilolog, 2010)
Glottodidactics is obviously to be seen as a rather new discipline, situated between the humanities and social sciences. This area of studies is delineated first of all by its object and research aims. Although there is a clear consensus about defining this object as L2 teaching/learning, it seems much harder to agree on how to structure this area in a tenable way. This article will argue in favor of organizing the field of glottodidactics in a way that would be propitious for the discipline as a whole, and for studies conducted within it. Further, a proposal is formulated to arrange this field around a central axis which could, in the author’s view, be the process of fostering learners’ communicative competence.